Laser powder bed fusion of bimetallic stainless steel/nickel-based superalloy: interface and mechanical properties - Fan, Haiyang (2023)
Potential applications of steel/nickel bimetals in corrosive environments are of increasing interest. In this study, bimetallic 316L/Hastelloy X was processed via laser powder bed fusion (L-PBF) using different parameters. Results indicated that the rapid cooling of L-PBF reduced the element segregation and carbide formation, thus leading to an interface free of cracks. However, also due to rapid solidification, the constituent elements of dissimilar materials at the interface were not mixed properly. With the increasing laser energy density, the interfacial width increased from dozens to hundreds of microns. The epitaxial grain growth from 316L to Hastelloy X was observed under the optimal processing parameters. The microhardness first declined at the front of the 316L side and then continuously increased in the interfacial region with the addition of Hastelloy X. During the tensile tests, the optimally built samples failed at the 316L side, implying the formation of solid bonding between the two metals.